Mechanical energy flow of the racket holding arm in the tennis serve focusing on the energy form - Murata, M.; Fujii, N.; Suzuki, Y. (International Journal of Sport & Health Science, 2022)
Mechanical energy is known to be transferred between a body segment and a joint. However, the transformation of this energy has not been classified. By focusing on the racket-holding arm during a tennis serve, the present study examined the transformation between translational and rotational energies due to the joint force, and investigated the kinetic chain from the viewpoint of energetics. Twenty-two tennis players were asked to perform flat services to the deuce side (i.e., the receiver`s right side), and the three-dimensional coordinates of reflective markers attached to each player and racket were collected with a motion capture system. The mechanical power acting on each segment and the mechanical energy generated/absorbed by each joint were divided into the following components: (1) STP = the time rate of change in the rotational energy of a segment due to the joint torque, (2) JTP = the generation/absorption of rotational energy due to the joint torque, (3) JFPt = the time rate of change in the translational energy of a segment due to the joint force, and (4) JFPr = the time rate of change in the rotational energy of a segment due to the moment of the joint force. The findings are summarized below.